Preparation method of Pt monatomic nano-enzyme and application of Pt monatomic nano-enzyme in cardiac troponin I detection

Pt single-atom nanozymes were prepared by Joule heat treatment and Se-doped Joule heat treatment, which solved the problems of insufficient catalytic activity and waste of precious metals in nanozymes, and achieved high efficiency of catalytic activity and low cost of detection.

CN121222447AActive Publication Date: 2025-12-30ZHEJIANG PROVINCIAL PEOPLES HOSPITAL

Patent Information

Application Number
CN202511786892.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-01
Publication Date
2025-12-30
Estimated Expiration
2045-12-01

AI Technical Summary

Technical Problem

Existing nanozymes have shortcomings in catalytic activity, especially in the detection of low-concentration analytes, which cannot meet the requirements of high-sensitivity detection. Traditional synthesis methods are cumbersome and have low utilization of precious metals, resulting in waste of precious metals.

Method used

A salt and urea-assisted Joule heat treatment process was used to construct Pt single-atom nanozymes on an oxide support. Combined with Se doping and rapid heating and cooling treatment, oxygen vacancies and hierarchical porous structures were formed, which improved the utilization and dispersion of precious metals and enhanced catalytic activity.

Benefits of technology

This study achieved efficient preparation of Pt single-atom nanozymes, improved catalytic activity and stability, enhanced the sensitivity of ELISA detection, and reduced production costs, demonstrating promising prospects for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121222447A_ABST
    Figure CN121222447A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of Pt monatomic nano-enzyme and application of Pt monatomic nano-enzyme in cardiac troponin I. The preparation method comprises the following steps: 1) ultrasonically dispersing cobalt salt, selenium powder, chloroplatinic acid, urea and sodium chloride in an alcohol solvent, heating and stirring until the solvent is completely volatilized to obtain a solid mixture, and grinding the solid mixture into powder; and 2) placing the powder in a heating device, carrying out Joule heat treatment in an air atmosphere, washing a reactant, and carrying out vacuum drying to obtain the Pt monatomic nano-enzyme. Se doping is introduced in the one-step chemical reaction process to construct oxygen vacancies, rapid heating and structural shaping are achieved in combination with Joule heat treatment, the Se-doped Co3O4-loaded Pt monatomic catalyst is obtained, the oxygen vacancies and Se doping sites are synergistically used as anchoring sites, Pt monatomic atoms are effectively fixed, and the loading capacity and dispersity of the Pt monatomic atoms are improved. The obtained material shows excellent POD-like enzyme activity, can be used for constructing a high-sensitivity colorimetric immunoassay system, and realizes rapid and accurate detection of cTnI.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of nanometer enzyme preparation, and particularly relates to a preparation method of a Pt single-atom nanometer enzyme and application thereof in detection of cardiac troponin I. BACKGROUND

[0002] Cardiac troponin I (cTnI) is an important biomarker for cardiovascular diseases such as acute myocardial infarction (AMI), and its level change provides key information for early diagnosis and prognosis evaluation of heart disease. Detecting the level of cTnI is crucial for timely detection of heart damage and guidance of clinical treatment. At present, enzyme-linked immunosorbent assay (ELISA) has been widely used in the detection of cardiac troponin I in clinic due to its high sensitivity and high specificity, and has achieved remarkable results. Traditional ELISA method relies on natural enzymes as signal amplification markers, but natural enzymes are sensitive to environmental factors, easy to inactivate, and have high production cost. Its catalytic efficiency and stability are difficult to meet the requirements of ultra-high sensitivity detection.

[0003] Nanometer enzyme has high stability, good adjustability and low cost, and can simulate the activity of natural enzyme, replace traditional natural enzyme in various biochemical reactions, and thus improve the detection sensitivity and efficiency. However, the existing nanometer enzyme still has deficiencies in catalytic activity, especially in the detection of low concentration analyte, its catalytic efficiency is difficult to meet the demand of high sensitivity detection.

[0004] Single-atom catalysts can significantly improve catalytic activity and selectivity by precisely positioning the catalytically active center to a single metal atom. Loading these single-atom catalysts onto oxide supports to form nanometer enzymes not only can further enhance catalytic activity and reaction stability, but also can effectively overcome the problem of insufficient catalytic efficiency of traditional nanometer enzymes, thereby significantly improving the efficiency of enzyme catalytic reaction and enhancing the sensitivity of ELISA detection. However, traditional synthesis methods usually need to prepare oxide supports first, and then load noble metal single atoms. This process is not only tedious and time-consuming, but also in the feeding process, part of the metal atoms cannot be effectively loaded on the carrier, resulting in low utilization rate of noble metal atoms. For example, a preparation method of single-atom peroxidase (POD) nanomaterials is disclosed in Chinese patent publication No. CN119114100B. The method reacts copper salt with amine compound by hydrothermal reaction to obtain defective metal oxide, and then mixes the oxide with Os salt, stirs, and then loads Os single atom on the oxide by impregnation method. Although this method can achieve a certain degree of single atom loading, the synthesis process is relatively complex, and in the impregnation process, due to the limited combination efficiency of metal oxide carrier and Os, it is difficult to fully utilize Os atoms, resulting in waste of noble metal and difficult to meet the requirements of industrial application.

[0005] Therefore, it is urgent to develop a simple, efficient and higher noble metal utilization rate synthesis method of metal oxide supported single-atom catalyst, so as to enable the metal oxide single-atom nanoscale enzyme to be better applied to the cTnI activity detection, improve the ELISA detection sensitivity based on the nanoscale enzyme, and promote its wide application in the diagnostic field. SUMMARY

[0006] In view of the problems existing in the prior art, the purpose of the present application is to provide a Pt single-atom nanoscale enzyme preparation method and its application in cardiac troponin I detection technical solution. The present application can solve the problems of complicated reaction steps, low single-atom loading, easy aggregation and migration, low catalyst activity and colorimetric immunoassay performance in the preparation of noble metal single-atom catalyst.

[0007] The first aspect of the present application is to provide a Pt single-atom nanoscale enzyme preparation method, which comprises the following steps: 1) ultrasonic dispersion of cobalt salt, selenium powder, chloroplatinic acid, urea and sodium chloride in an alcohol solvent, then heating and stirring until the alcohol solvent is completely volatilized, obtaining a solid mixture and grinding into a powder; 2) transferring the powder to a quartz crucible and placing it in the graphite sample table groove of the joule heat rapid heating device, and performing joule heat treatment in an air atmosphere, and after centrifugation, washing and vacuum drying of the reaction product, obtaining the Pt single-atom nanoscale enzyme.

[0008] Further, in step 1), cobalt dichloride is selected as the cobalt salt, and ethanol is selected as the alcohol solvent.

[0009] Further, in step 1), the amount ratio of cobalt salt, selenium powder, chloroplatinic acid, urea, sodium chloride and alcohol solvent is: 1 mmol: 7-12 mmol: 0.002-0.007 mmol: 140-180 mmol: 30-50 mmol: 40-60 mL.

[0010] Further, in step 1), the heating temperature is 50-80℃.

[0011] Further, in step 2), the joule heat treatment conditions are: heat treatment temperature 500-800℃, heating rate 1500-3000℃ / s, and joule heat treatment times 2-7 times, wherein, the room temperature is raised to the target temperature, and then naturally cooled to room temperature for one joule heat treatment.

[0012] Further, in step 2), the washing conditions are: deionized water centrifugation, washing 3-5 times, vacuum drying temperature is 40-80℃, and drying time is 5-10h.

[0013] The second aspect of the present application is to provide a Pt single-atom nanoscale enzyme prepared by the above preparation method.

[0014] Further, the platinum is dispersed in the form of single atoms on a selenium-doped Co3O4 support having oxygen vacancies and a hierarchical pore structure.

[0015] Further, the specific surface area of the Pt single-atom nanozyme is not less than 60 m² / g.

[0016] The third aspect of the present application is to provide the use of the Pt single-atom nanozyme in the preparation of a reagent for detecting cardiac troponin I.

[0017] Compared with the prior art, the present application has the following beneficial effects: 1) The present application uses a salt and urea assisted Joule heat treatment process to realize the construction of oxide supported single atoms. Compared with the traditional high temperature calcination method, this process does not require complex steps, is simple to operate, has high catalyst preparation efficiency and low energy consumption. At the same time, this method significantly improves the utilization rate of noble metal precursors, avoids metal waste, and effectively enhances the dispersion and stability of noble metal single atoms on the oxide support, showing good prospects for industrial application.

[0018] 2) The present application introduces Se doping to construct oxygen vacancies in a one-step synthesis process, and combines Joule heat treatment to realize rapid heating and cooling during the synthesis process, thereby effectively improving the defect concentration of the support and the loading, dispersion and stability of the Pt single atoms. Joule heat treatment has the characteristics of rapid heating and cooling, which can stabilize the oxygen vacancies during crystal formation, thereby significantly enhancing the binding strength between the Pt single atoms and the support. At the same time, due to the extremely rapid heating and cooling process, the Pt element does not form obvious agglomeration, thereby realizing efficient single atom dispersion and overcoming the problem of metal agglomeration under traditional calcination conditions.

[0019] 3) The present application uses urea to form a stable chelate with Pt and Co ions, enabling the metal elements to be highly uniformly distributed at the molecular level. During pyrolysis, urea decomposes to release gas and generate a carbon-based sacrificial template, providing reaction sites for the nucleation and growth of Se-doped Co3O4 crystals and inducing the formation of a hierarchical pore structure inside the material. The resulting support has a significantly increased specific surface area, providing abundant anchoring sites for Pt single atoms, which is conducive to the fixation and retention of single atoms, and also endows the catalyst with good structural stability and high activity.

[0020] 4) The present application introduces sodium chloride into the system, which forms a polar chemical environment during heat treatment, effectively inhibiting the agglomeration of Pt atoms and promoting their single atom dispersion on the support surface. This polar environment also improves the stability of the defects on the support surface, further improving the uniformity and stability of Pt single atom loading, providing a guarantee for the construction of high-performance single atom catalysts.

[0021] 5) The prepared Se-doped Co3O4 supported Pt single-atom nanozyme has an ultra-high specific surface area (65.27 m² / g), rich oxygen vacancies and uniformly dispersed Pt single atoms, and exhibits excellent POD catalytic activity. In the colorimetric immunoassay detection of cardiac troponin I, the nanozyme achieves an extremely low detection limit (LOD 2.1 pg / mL), indicating that the material not only has outstanding advantages in basic catalytic performance, but also exhibits extremely high sensitivity and application potential in biological detection applications. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 X-ray powder diffraction (XRD) pattern of the sample of Example 1; Figure 2 Scanning electron microscope (SEM) and element distribution (EDS Mapping) pattern of the sample of Example 1; Figure 3 Scanning transmission electron microscope (STEM) pattern of the sample of Example 1; Figure 4 Full-automatic specific surface area and porosity analyzer (BET) pattern of the sample of Example 1; Figure 5 Electron paramagnetic resonance (EPR) pattern of the sample of Example 1; Figure 6 POD performance test pattern of the sample of Example 1; Figure 7 and Figure 8 Colorimetric immunoassay pattern of the sample of Example 1. DETAILED DESCRIPTION

[0023] The present application will be further described below in conjunction with specific examples, so as to better understand the technical solutions.

[0024] Example 1

[0025] (1) 1 mmol of CoCl2, 9 mmol of selenium powder, 0.006 mmol of H2PtCl6, 160 mmol of urea and 40 mmol of NaCl were ultrasonically dispersed in 50 mL of ethanol, then stirred at 60°C until the ethanol was completely volatilized, and the remaining solid was ground into powder to obtain a first solid A.

[0026] (2) The first solid A was transferred to a quartz crucible and placed in the groove of the graphite sample table of the Joule heat rapid heating device, and subjected to 4 times of Joule heat treatment under an air atmosphere, with a treatment temperature of 600°C and a heating rate of 2300°C / s. The remaining solid was washed by centrifugation with deionized water for 4 times, and then vacuum dried at 60°C for 8 hours to obtain a Se-doped Co3O4 supported Pt single-atom nanozyme.

[0027] The product prepared in Example 1 was characterized: The XRD pattern is shown in Figure 1 The results show that the characteristic diffraction peaks in the figure are highly consistent with the standard card PDF #00-009-0418, indicating that the sample is composed of Co3O4 phase.

[0028] The SEM image is shown in Figure 2 The results show that Se, Co and O are uniformly distributed in the sample, indicating that Se is successfully doped into Co3O4.

[0029] The STEM image is shown in Figure 3 The results show that Pt single atoms are atomically dispersed on the Se-doped Co3O4 carrier.

[0030] The BET image is shown in Figure 4 The results show that the sample has a clear hysteresis loop, indicating that the material has abundant mesoporous structure and large specific surface area, reaching 65.27 m² / g.

[0031] The EPR image is shown in Figure 5 The results show that the sample has a strong EPR signal peak at g=2.003, indicating that there are abundant oxygen defects in the sample.

[0032] In summary, the sample prepared in Example 1 is composed of Se-doped Co3O4 and Pt single atoms, has abundant mesoporous structure and oxygen defects, and the atomic dispersion of Pt and oxygen defects enhance the active sites. At the same time, the mesoporous structure and large specific surface area increase the contact area of reactants, which overall improves the catalytic performance of the sample in the POD reaction.

[0033] The sample prepared in Example 1 was tested for POD activity, and the test method was as follows: Se-doped Co3O4 supported Pt single atom nanoszyme suspension (1 mg / mL), TMB (1 mM) and H2O2 (80 mM) solutions were prepared with pure water. Subsequently, 50 μL Se-doped Co3O4 supported Pt single atom nanoszyme, 150 μL H2O2 and 200 μL TMB were mixed in 2600 μL sodium acetate-acetic acid (NaAc-HAc, pH=4.5, 0.2 M) buffer solution, and after incubation at room temperature for 20 minutes, the absorbance of the reaction solution was measured at 652 nm using a UV-visible spectrophotometer, thereby evaluating the activity of Se-doped Co3O4 supported Pt single atom nanoszyme.

[0034] The test results are shown in Figure 6 Figure 6 ​The POD enzyme activity of the samples prepared in Examples 2-3 and Comparative Examples 1-5 was also compared. Figure 6 It can be seen that the order of the absorption peak intensity at 652 nm represents the order of POD enzyme activity. The results are: Example 1 > Example 3 > Example 2 > Comparative Example 4 > Comparative Example 5 > Comparative Example 1 > Comparative Example 3 > Comparative Example 2. This shows that the Se-doped Co3O4-loaded Pt single-atom nanozyme (Example 1 sample) prepared under the synthesis conditions of Example 1 has the best POD activity.

[0035] The samples obtained in Example 1 were subjected to colorimetric immunoassay, and the test method is as follows: 2 μL of monoclonal antibody mAb1 (12 μg / mL) was mixed with 50 μL of PBS-Tween solution and added to the wells of a 96-well plate, then incubated at 4°C for 12 hours. Subsequently, the plate was washed with 10 mM PBS buffer (containing 0.05% Tween 20, pH 7.4) to remove excess mAb1. Next, unbound nonspecific binding sites were blocked with 1% (w / v) bovine serum albumin (BSA), and the plate was washed again with PBS buffer to remove excess BSA. 50 μL of human serum sample was added to each well and incubated at 37°C for 120 minutes. Then, 50 μL of pAb2-SiO2-ALP (12 μg / mL) was added and incubated at 37°C for 60 minutes. After each incubation, the plate was washed three times with PBS buffer. Next, 50 μL of 1.0 mM ascorbic acid 2-phosphate (AAP) solution was added to each well, and the mixture was incubated at 37°C for 60 minutes. ALP catalyzed the conversion of AAP to ascorbic acid (AA). Finally, the enzymatic product generated from the reaction was transferred to the Example 1 sample-TMB solution, which consisted of 50 μL of Example 1 sample (1 mg / mL), 50 μL of TMB (10 mM), and 200 μL of H2O2 (20 mM). The absorbance of the colorimetric reaction was finally measured at a wavelength of 652 nm.

[0036] Test results are as follows Figure 7 and Figure 8 As shown, by Figure 7 It can be seen that within the low concentration range of cTnI, the absorbance of the colorimetric reaction gradually decreases with increasing cTnI concentration; while within the high concentration range of cTnI, the absorbance of the colorimetric reaction changes less, indicating that high concentrations of cTnI can fully trigger the enzymatic reaction, and the generated product effectively reduces oxidized TMB (ox-TMB). Figure 8It can be seen that the response of the target signal is negatively correlated with the absorbance of the sample of Example 1-TMB solution, and shows a good linear relationship in the dynamic range of 0.003 to 70 ng / mL. The fitting equation is: Y = -0.28947 x lg C[cTnI] + 0.63631 (R² = 0.99692, n = 12), and the detection limit is 2.1 pg / mL. This indicates that the linear range and LOD of the sample of Example 1 in colorimetric immunoassay have excellent performance.

[0037] Example 2

[0038] (1) 1 mmol of CoCl2, 7 mmol of selenium powder, 0.002 mmol of H2PtCl6, 140 mmol of urea, and 30 mmol of NaCl were ultrasonically dispersed in 40 mL of ethanol, then stirred at 50°C until the ethanol was completely volatilized, and the remaining solid was ground into powder to obtain a first solid A.

[0039] (2) The first solid A was transferred to a quartz crucible and placed in the groove of the graphite sample table of the Joule heat rapid heating device, and subjected to 2 times of Joule heat treatment under air atmosphere, with a treatment temperature of 800°C and a heating rate of 1500°C / s. The remaining solid was centrifuged with deionized water, washed 3 times, and vacuum dried at 40°C for 10 h to obtain Se-doped Co3O4 supported Pt single-atom nanozyme.

[0040] The sample prepared in Example 2 was subjected to XRD and BET tests, and the test results are shown in Table 1.

[0041] As can be seen from Table 1, the XRD test results of the sample of Example 2 show that the sample is composed of Co3O4 phase, which is consistent with the phase composition of the sample of Example 1. In addition, the BET test results of the sample of Example 2 show that the sample also has abundant mesoporous structure and large specific surface area, and the specific surface area is 60.82 m² / g.

[0042] The sample prepared in Example 2 was subjected to POD activity test and colorimetric immunoassay, and the test results are shown in Figure 6 and Table 1.

[0043] As can be seen from Figure 6 and Table 1, the sample of Example 2 has better POD enzyme activity than the sample of the comparative example, with an LOD of 4.7 pg / mL, which is significantly lower than that of the sample of the comparative example. This indicates that the Se-doped Co3O4 supported Pt single-atom nanozyme under the synthesis conditions of Example 2 has good POD activity.

[0044] Example 3

[0045] (1) 1 mmol CoCl2, 12 mmol selenium powder, 0.007 mmol H2PtCl6, 180 mmol urea, 50 mmol NaCl were ultrasonically dispersed in 60 mL ethanol, then stirred at 80°C until the ethanol was completely volatilized, and the remaining solid was ground into powder to obtain a first solid A.

[0046] (2) The first solid A was transferred to a quartz crucible and placed in the groove of the graphite sample table of the joule heat rapid heating device, and subjected to 7 joule heat treatments under an air atmosphere, with a treatment temperature of 500°C and a temperature rise rate of 3000°C / s. The remaining solid was centrifuged with deionized water, washed 5 times, and vacuum dried at 80°C for 5 h to obtain Se-doped Co3O4 supported Pt single-atom nanoszyme.

[0047] The sample prepared in Example 3 was subjected to XRD and BET tests, and the test results are shown in Table 1.

[0048] As can be seen from Table 1, the XRD test results of the sample of Example 3 show that the sample is composed of Co3O4 phase, which is consistent with the phase composition of the sample of Example 1. In addition, the BET test results of the sample of Example 3 show that the sample also has abundant mesoporous structure and large specific surface area, and the specific surface area is 67.41 m² / g.

[0049] The sample prepared in Example 3 was subjected to POD activity test and colorimetric immunoassay, and the test results are shown in Figure 6 and Table 1.

[0050] As can be seen from Figure 6 and Table 1, the absorbance of the sample of Example 3 at 652 nm is 0.2486, the peroxidase-like activity is better than that of the comparative sample, and the LOD is 3.4 pg / mL, which is significantly lower than that of the comparative sample. It shows that the Se-doped Co3O4 supported Pt single-atom nanoszyme under the synthesis conditions of Example 3 also has good POD activity.

[0051] Comparative Example 1 Comparative Example 1 differs from Example 1 in that no selenium powder is added in step (1), and the others remain unchanged.

[0052] The sample prepared in Comparative Example 1 was subjected to XRD, BET and EPR tests, and the test results are shown in Table 1 and Figure 5 (EPR).

[0053] The XRD test results of the sample of Comparative Example 1 show that the sample is composed of Co3O4 and Pt phases, indicating that Pt in Comparative Example 1 exists in the form of nanoparticles rather than Pt single atoms. In addition, the specific surface area of the sample of Comparative Example 1 is 59.75 m² / g, which is much lower than the test results of the sample of Example 1. The EPR signal peak intensity presented by the sample of Comparative Example 1 at g = 2.003 is also weaker than that of the sample of Example 1 Figure 5 , which indicates that the oxygen defect content of the sample of Comparative Example 1 is much lower than that of the sample of Example 1, and the main reason is that Se doping in the example can partially replace the O element position in Co3O4, thereby forming oxygen vacancies.

[0054] POD activity test and colorimetric immunoassay were performed on the sample of Comparative Example 1, and the POD performance test method was the same as that of the sample of Example 1. The test results are shown in Figure 6 and Table 1.

[0055] From Figure 6 and Table 1, it can be seen that the absorbance of Comparative Example 1 at 652 nm is 0.1346, and its POD-like activity is significantly lower than that of the sample of Example 1. At the same time, its LOD is 77.5 pg / mL, which is much higher than that of the sample of Example 1. The above results show that undoped Se can reduce the number of oxygen vacancies, so that Pt cannot be dispersed at the atomic level, but forms Pt nanoparticles, significantly reducing the number of Pt active sites, and ultimately leading to weakened enzyme activity.

[0056] Comparative Example 2 Comparative Example 2 is different from Example 1 in that no chloroplatinic acid is added in step (1), and the others are the same.

[0057] XRD and BET tests were performed on the sample of Comparative Example 2, and the test results are shown in Table 1.

[0058] From Table 1, it can be seen that the sample prepared in Comparative Example 2 is composed of Co3O4 phase. In addition, similar to the sample of Example, the specific surface area of the sample of Comparative Example 2 is 58.98 m² / g, indicating that the sample of Comparative Example 2 has a high specific surface area.

[0059] POD activity test and colorimetric immunoassay were performed on the sample prepared in Comparative Example 2, and the POD performance test method was the same as that of the sample of Example 1. The test results are shown in Figure 6 and Table 1.

[0060] From Figure 6 and Table 1, it can be seen that the absorbance of Comparative Example 2 at 652 nm is 0.1788, and its peroxidase-like activity is lower than that of the sample of Example 1. And the LOD is 110.3 pg / mL, which is much higher than that of the sample of Example 1. This indicates that Pt single atoms are the main POD nanenzyme active sites in the example.

[0061] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no urea was added in step (1), while everything else remained the same.

[0062] The samples prepared from the three comparative examples were subjected to XRD and BET tests, and the test results are shown in Table 1.

[0063] As shown in Table 1, the XRD results of the sample prepared in Comparative Example 3 indicate that the sample consists of Co3O4 and Pt phases, suggesting that the Pt in Comparative Example 3 exists in the form of nanoparticles rather than single Pt atoms. Furthermore, the specific surface area of ​​the sample in Comparative Example 3 is 33.36 m² / g, which is significantly lower than the test results of the sample in Example 1. In the absence of urea, the dispersion of Pt and Co ions is poor, and the lack of gas generation and carbon-based template results in insufficient pore structure and specific surface area of ​​the Se-doped Co3O4, thus causing Pt to exist in the form of nanoparticles rather than single Pt atoms.

[0064] The sample prepared in Comparative Example 3 was subjected to POD activity testing and colorimetric immunoassay. The POD performance testing method was the same as that used for the sample in Example 1. The test results are shown in [Figure 1]. Figure 6 See Table 1.

[0065] Depend on Figure 6 As shown in Table 1, the absorbance of Comparative Example 3 sample at 652 nm was 0.13, indicating that its POD activity was lower than that of the Example sample. Furthermore, its LOD was 92.6 pg / mL, significantly higher than that of the Example sample. This suggests that urea effectively disperses Pt and Co ions by chelating with metal ions. During high-temperature calcination, urea decomposes to generate gas and forms a carbon-based template, promoting the uniform dispersion of Se-doped Co3O4, increasing the pore structure and specific surface area, and simultaneously contributing to the uniform distribution of Pt single atoms. These changes not only optimize the material structure but also significantly enhance the POD activity.

[0066] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that sodium chloride was not added in step (1), while everything else remained the same.

[0067] The samples prepared in Comparative Example 4 were subjected to XRD, BET, and EPR tests, respectively. The test results are shown in Table 1 and 2. Figure 5 (EPR).

[0068] As shown in Table 1, the XRD results of Comparative Example 4 indicate that the sample consists of Co3O4 and Pt phases, suggesting that the Pt in Comparative Example 4 exists in the form of nanoparticles rather than single Pt atoms. Furthermore, the specific surface area of ​​Comparative Example 4 is 50.23 m² / g, lower than that of Example 1. Compared to Example 1, the EPR signal peak of Comparative Example 4 at g=2.003 is weaker (…). Figure 5The results indicate that the oxygen defect concentration in Comparative Example 4 was lower than that in Example 1. This is mainly because the addition of sodium chloride created a polar chemical environment during the heat treatment process, which not only effectively suppressed the aggregation of Pt atoms but also promoted their single-atom dispersion on the support surface. This polar environment also improved the stability of defects on the support surface, thereby further improving the uniformity and stability of Pt single-atom loading and providing a guarantee for the construction of high-performance single-atom catalysts.

[0069] The sample prepared in Comparative Example 4 was subjected to POD activity testing and colorimetric immunoassay. The POD performance testing method was the same as that used for the sample in Example 1. The test results are shown in [Figure 1]. Figure 6 See Table 1.

[0070] from Figure 6 As shown in Table 1, the absorbance of Comparative Example 4 sample at 652 nm was 0.12, indicating that its peroxidase-like activity was lower than that of the Example sample. Simultaneously, its LOD was 40.2 pg / mL, significantly higher than that of the Example sample. These results suggest that the absence of sodium chloride resulted in Pt existing in nanoparticle form rather than as single Pt atoms, which simultaneously reduced the oxygen vacancy concentration in the carrier. This significantly reduced the number of active sites in Comparative Example 4 sample, ultimately leading to weakened enzyme activity.

[0071] Comparative Example 5 The difference between Comparative Example 5 and Example 1 lies in the heating device used in step (1). The Joule heating device is replaced with a muffle furnace, while the other steps remain unchanged. The specific operation is as follows: The first solid A was transferred to a quartz crucible and placed in a muffle furnace for calcination in air atmosphere at a temperature of 600℃ and a heating rate of 5℃ / min. The reaction was held at this temperature for 1 hour. The remaining solid was centrifuged with deionized water, washed four times, and vacuum dried at 60℃ for 8 hours to obtain the comparative sample 5.

[0072] XRD, BET, and EPR tests were performed on the five comparative samples, and the results are shown in Table 1 and 2. Figure 5 (EPR).

[0073] As shown in Table 1, the XRD results of Comparative Example 5 indicate that the sample consists of Co3O4 and Pt phases, suggesting that the Pt in Comparative Example 5 exists in the form of nanoparticles rather than single Pt atoms. Furthermore, the specific surface area of ​​Comparative Example 5 is 45.30 m² / g, significantly lower than that of Example 1. The EPR signal peak intensity of Comparative Example 5 at g=2.003 is weaker than that of Example 1. Figure 5), which is mainly because the Joule heat treatment has the characteristics of rapid heating and cooling, which can avoid the sintering of Se-doped Co3O4 caused by long time high temperature calcination, and stabilize the oxygen vacancies in the process of Se-doped Co3O4 formation, thereby significantly enhancing the binding strength between Pt single atom and Se-doped Co3O4 carrier. At the same time, due to the extremely rapid heating and cooling process, Pt elements do not occur obvious agglomeration, thereby realizing high-efficiency single atom dispersion.

[0074] POD activity test was performed on the sample of Comparative Example 5, and the POD performance test method was the same as that of the sample of Example 1. The test results are shown in Table 1. Figure 6 and Table 1.

[0075] From Figure 6 and Table 1, it can be seen that the absorbance of the sample of Comparative Example 5 at 652 nm is 0.1134, and its peroxidase-like activity is lower than that of the samples of Examples 1-3. At the same time, the LOD is 68.7 pg / mL, which is much higher than that of the sample of Example 1. This is mainly because, compared with Comparative Example 5, the sample of Example has a higher specific surface area and rich oxygen vacancies, which are all conducive to the adsorption of reactants and the desorption of products in the process of enzyme catalytic reaction. In addition, the Pt single atom in the sample of Example can expose more active sites, so that the sample of Example exhibits more excellent POD catalytic activity and has a lower detection limit of cardiac troponin I.

[0076] Table 1 Name XRD BET(m 2 / g) Limit of detection (pg / mL) Example 1 Co304, Pt monatomic 65.27 2.1 Example 2 Co304, Pt monatomic 60.82 4.7 Example 3 Co304, Pt monatomic 67.41 3.4 Comparative Example 1 Co304, Pt nanoparticles 59.75 77.5 Comparative Example 2 Co304 58.98 110.3 Comparative Example 3 Co304, Pt nanoparticles 33.36 92.6 Comparative Example 4 Co304, Pt nanoparticles 50.23 40.2 Comparative Example 5 Co304, Pt nanoparticles 45.30 68.7 .

Claims

1. A method for preparing a Pt single-atom nanoszyme, characterized in that, The preparation method comprises the following steps: 1) ultrasonic dispersion of cobalt salt, selenium powder, chloroplatinic acid, urea and sodium chloride in an alcohol solvent, then heated and stirred until the alcohol solvent is completely volatilized, to obtain a solid mixture and grind into a powder; 2) transfer the powder to a quartz crucible and place it in the groove of the graphite sample table of the joule heat rapid heating device, and perform joule heat treatment in an air atmosphere, and after centrifugation, washing and vacuum drying of the reaction product, a Pt single-atom nanozyme is obtained.

2. The method for preparing a Pt single-atom nanoszyme according to claim 1, wherein, In step 1), cobalt dichloride is selected as the cobalt salt, and ethanol is selected as the alcohol solvent.

3. The method for preparing a Pt single-atom nanozyme as described in claim 1, characterized in that, In step 1), the amount ratio of cobalt salt, selenium powder, chloroplatinic acid, urea, sodium chloride and alcohol solvent is: 1 mmol: 7-12 mmol: 0.002-0.007 mmol: 140-180 mmol: 30-50 mmol: 40-60 mL.

4. The method for preparing a Pt single-atom nanozyme as described in claim 1, characterized in that, In step 1), the heating temperature is 50-80℃.

5. The method for preparing a Pt single-atom nanozyme as described in claim 1, characterized in that, In step 2), the joule heat treatment conditions are: heat treatment temperature 500-800℃, heating rate 1500-3000℃ / s, and joule heat treatment times 2-7 times, wherein, the room temperature is raised to the target temperature, and then naturally cooled to room temperature for one joule heat treatment.

6. The method for preparing a Pt single-atom nanozyme as described in claim 1, characterized in that, In step 2), the washing conditions are: deionized water centrifugation, washing 3-5 times, vacuum drying temperature is 40-80℃, and drying time is 5-10h.

7. The Pt single-atom nanozyme prepared by any one of the preparation methods of claims 1-6.

8. The Pt single-atom nanoszyme of claim 7, wherein, The platinum is dispersed in the form of single atoms on a selenium-doped Co3O4 carrier, and the carrier has oxygen vacancies and a hierarchical pore structure.

9. The Pt single atom nanoszyme of claim 8, wherein, The specific surface area of the Pt single-atom nanozyme is not less than 60 m² / g.

10. Use of the Pt single-atom nanozyme of claim 7 in the preparation of a reagent for detecting cardiac troponin I.

Citation Information

Patent Citations

  • A single-atom POD-mimicking enzyme nanomaterial, its preparation method, and food safety detection application

    CN119114100B

  • Monatomic nano-enzyme Pt (at) MoS2 as well as preparation method and application thereof

    CN115192606A

  • Preparation method and application of multifunctional monatomic nano-enzyme

    CN117797169A

  • Preparation method and application of cobalt defect type cobalt selenide anchored high-load Pt monatomic catalyst

    CN118287112A

  • Preparation method and application of Mn3O4-loaded porous lithium-sulfur battery composite material rich in carbon defects

    CN118825184A

Cited By

  • Rapid preparation method and application of hierarchical porous carrier loaded atomic-scale dispersion high-stability Ru-based nano-enzyme

    CN121755225A

  • A rapid preparation method and application of hierarchical porous carrier loaded atomically dispersed high-stable Ru-based nanoszyme

    CN121755225B

  • High-load Pt monatomic nano-enzyme as well as preparation method and application thereof

    CN121755233A

  • Preparation method and application of porous RuO2 nano-enzyme for detecting creatinine

    CN121988317A